Upaya Peningkatan Keterampilan Srart Jongkok Menggunakan Media Block Start Cabang Lari Sprint pada Siswa Kelas XI BKP SMK Negeri 2 Karang Baru - Muhammad Hatta (Tematik: Jurnal Penelitian Pendidikan Dasar, 2022)
The aims of this study were to: 1) Improve students' learning skills in starting the sprint running by using a block start in physical education lessons. 2) Introducing the media block start and its function as a tool used by runners. This type of research is classroom action research (Classroom Action Research) with a qualitative approach, with the research subjects of class XI students in the Construction and Property Business at SMK Negeri 2 Karang Baru. Learning is done by applying Block start media in physical education learning. The data obtained in the field were processed using qualitative and quantitative methods. From the results of data processing, it can be concluded that learning outcomes have increased both individually and classically, but still have not reached the expected level of classical completeness. The teacher's ability to manage learning using Block start media during cycle 1 and cycle 2 has increased from the low category to the very high category. The indicators in this study are: (1) if 75% of the number of students are categorized as complete with the criteria of complete learning if the value of the evaluation results in cycles I, II, 65, (2) if student activity in learning is 75% as measured by looking at student observation sheets. The results of the research in the first cycle showed that the average student learning outcomes were 68.26 and the percentage of learning completeness was 65.22%. Student activity was 47.73% at the first meeting and 63.64% at the second meeting, the percentage of teacher ability was 74.78% at the first meeting and 78.26% at the second meeting. While the results of the research in the second cycle the average student learning outcomes were 74.78 and the percentage of learning completeness was 71.72%. The student activity is 75.00%, and the percentage of the teacher's ability is 84.37%. From this study, it can be concluded that Block Start Japat improves Sprint Start Sprint Branch skills in Class XI BKP students of SMK Negeri 2 Less New.